Determinantes ecológicos, evolutivos e histórico-biogeográficos dos padrões de diversidade de mamíferos terrestres em diferentes escalas - Peixoto, Franciele Parreira (2017)
The concept of ecological niche describes the set of biotic and abiotic conditions for which the species can maintain populations and define the species geographical range. The ecological niche is multidimensional, which means that is a function of several species characteristics. These characteristics can change fastly or can vary very slowly, remaining conserved throughout the evolutionary time, which characterizes the niche conservatism (i.e., the tendency of the species retaining the ancestral niche along the evolutionary time). Retaining the ancestral niche implies a smaller group capacity. Retaining the ancestral niche implies that the group is less able to adapt outside the distribution boundaries defined by the ecological niche. Therefore, the way that characteristics linked to the niche evolved along the time is determinant to generate differential patterns of diversity among taxa. In fact, niche conservatism has been raised as a relevant factor to explain the latitudinal gradient of diversity, as well as the biota formation of different habitats. Conservation of ecological tolerances implies an inheritance of a limited ability to colonize and establish in different habitats. On the other hand, some groups can be ecologically more flexible and colonize new habitats through the niche evolution, probably related to specific functional adaptations that allow the establishment of species. The objective of this work was to evaluate the diversity patterns of terrestrial mammals to infer about the main ecological, evolutionary and historical-biogeographical processes.